2009
DOI: 10.15288/jsad.2009.70.186
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Treatment Effects on Secondary Nondrinking Outcomes and Quality of Life: The COMBINE Study

Abstract: ABSTRACT. Objective:To evaluate the full range of alcohol treatment effectiveness, it is important to assess secondary nondrinking outcome dimensions in addition to primary alcohol consumption outcomes. Method: We used a large sample (n = 1,226) of alcoholdependent participants entering the National Institute on Alcohol Abuse and Alcoholism-sponsored COMBINE (Combining Medications and Behavioral Interventions) Study, a multisite clinical trial of pharmacological (naltrexone [ReVia] and acamprosate [Campral]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 40 publications
8
53
2
1
Order By: Relevance
“…Thus, maintenance of abstinence led to an improvement of OQOL that involved the patients' environment, social relationships, physical health and, to a lesser extent, psychological health. These findings were consistent with those of previous short-term studies [3-5, 7, 8, 10] and supported the findings of the long-term COMBINE study [17]. In the present study, OQOL among abstinent patients was particularly improved at 6 months after discharge, whereas OQOL was merely maintained at 12 months after discharge.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, maintenance of abstinence led to an improvement of OQOL that involved the patients' environment, social relationships, physical health and, to a lesser extent, psychological health. These findings were consistent with those of previous short-term studies [3-5, 7, 8, 10] and supported the findings of the long-term COMBINE study [17]. In the present study, OQOL among abstinent patients was particularly improved at 6 months after discharge, whereas OQOL was merely maintained at 12 months after discharge.…”
Section: Discussionsupporting
confidence: 93%
“…Foster et al [50] reported a similar weak baseline correlation between alcohol dependence severity and QOL using a more subjective assessment tool (i.e., LSS). LoCastro et al [17] also found correlations at the 6-and 12-month follow-ups, but these were weaker than those described here. However, despite using the same QOL evaluation tool, the previous study employed a different alcohol use severity assessment.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations